EZH2 enhances the differentiation of fibroblasts into myofibroblasts in idiopathic pulmonary fibrosis. Issue 17 (31st August 2016) - Xiao, Xiao; Senavirathna, Lakmini K.; Gou, Xuxu; Huang, Chaoqun; Liang, Yurong; Liu, Lin
Abstract: The accumulation of fibroblasts/myofibroblasts in fibrotic foci is one of the characteristics of idiopathic pulmonary fibrosis (IPF). Enhancer of zeste homolog 2 (EZH2) is the catalytic component of a multiprotein complex, polycomb repressive complex 2, which is involved in the trimethylation of histone H3 at lysine 27. In this study, we investigated the role and mechanisms of EZH2 in the differentiation of fibroblasts into myofibroblasts. We found that EZH2 was upregulated in the lungs of patients with IPF and in mice with bleomycin‐induced lung fibrosis. The upregulation of EZH2 occurred in myofibroblasts. The inhibition of EZH2 by its inhibitor 3‐deazaneplanocin A (DZNep) or an shRNA reduced the TGF‐ β 1‐induced differentiation of human lung fibroblasts into myofibroblasts, as demonstrated by the expression of the myofibroblast markers α ‐smooth muscle actin and fibronectin, and contractility. DZNep inhibited Smad2/3 nuclear translocation without affecting Smad2/3 phosphorylation. DZNep treatment attenuated bleomycin‐induced pulmonary fibrosis in mice. We conclude that EZH2 induces the differentiation of fibroblasts to myofibroblasts by enhancing Smad2/3 nuclear translocation. Abstract : Enhancer of zeste homolog 2 (EZH2) is upregulated in the lungs of patients with idiopathic pulmonary fibrosis (IPF). EZH2 induces the differentiation of fibroblasts to myofibroblasts by enhancing Smad2/3 nuclear translocation.